Determinants of customer satisfaction on retail banks in New Zealand: an empirical analysis using structural equation modeling - Abdullah, Moha Asri; Abd. Manaf, Noor Hazilah; Yusuf, Bashir; Ahsan, Kamrul (World Business Institute, 2014)
Customer retention is very crucial to the continuous survival of retail banking anywhere in the world, most especially when the deregulation of the sector has provided the customers with different choices to satisfy their financial needs. This has made many banks to pursue different strategies that will increase their customer satisfaction through enhanced service quality. This study examined the determinants of retail bank customer satisfaction in New Zealand through the survey of their perception about the banks service quality. The five dimensions of service quality were initially analysed in relation to customer satisfaction using the structural equation modeling technique but three were eventually used. The three factors specified to determine customer satisfaction in retail banking were found to be both practically and statistically significant. The implication is that the core, the enabling and the relational aspect of service quality must be taken care of to satisfy their customers in order to retain their loyalty.